2008
DOI: 10.1007/s10661-008-0416-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment

Abstract: The Ria de Aveiro (Portugal) is a coast al lagoon adjacent to the Atlantic Ocean and it has an inner bay (Laranjo bay) that received a highly contaminated effluent discharged by a mercury cell chlor-alkali plant from the 1950s until 1994. The aim of this study is to review in a holistic way several research studies that have been carried out in the Ria de Aveiro, in order to evaluate the remobilization of the mercury accumulated within the system and the recovery of the lagoon. The spatial distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(68 citation statements)
references
References 28 publications
4
60
0
1
Order By: Relevance
“…In fact, P. ulvae is the responsible for the mean annual incorporation of approximately 15 g of mercury in an area of 0.6 Km 2 . This value may seem negligible when comparing with the large amount of mercury accumulated in the Laranjo Bay sediments (z30 tons; Pereira et al, 2009). However, if we consider the other species that are directly associated to this gastropod, this value can have a strong relevance in terms of mercury biomagnification.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, P. ulvae is the responsible for the mean annual incorporation of approximately 15 g of mercury in an area of 0.6 Km 2 . This value may seem negligible when comparing with the large amount of mercury accumulated in the Laranjo Bay sediments (z30 tons; Pereira et al, 2009). However, if we consider the other species that are directly associated to this gastropod, this value can have a strong relevance in terms of mercury biomagnification.…”
Section: Discussionmentioning
confidence: 94%
“…chlor-alkali production processes) as well as in other countries (Zagury et al 2006;Dufault et al 2009;Esbrí et al 2014) have been using mercury and its compounds in manufacturing processes, which resulted in high concentrations of mercury in nearby soils. This poses potential health and environmental risk over a much wider area Pereira et al 2009). The most popular remediation technologies for mercury contaminated soils are: liquid extraction, thermal treatment, electrolytic methods, mercury flotation or immobilisation and solidification/stabilisation (S/S).…”
Section: Introductionmentioning
confidence: 99%
“…The mesohaline-oligohaline muddy-sandy habitats were classified as 'Good-Moderate EcoQS', while the oligohaline-limnetic muddy-sand habitats were evaluated as 'Moderate' to 'Bad EcoQS'. In addition, Nunes et al (2008) performed a more detailed study restricted to the historical contamination in the 2 km 2 Laranjo basin area close to Estarreja (Figure 17.5), concluding that macrobenthic community structure changed significantly along the mercury gradient (for a more detailed information regarding the Hg historical contamination see Pereira et al (2009)). Results showed that the increase of mercury contamination was associated with reduced total abundance, lower species diversity dominance of taxa tolerant to mercury (Nunes et al 2008).…”
Section: A Comparative View Of Ecoqs In the Four Lagoonsmentioning
confidence: 98%